2006
DOI: 10.1021/ja0613613
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Oligo-α-(2,8)-Sialic Acids

Abstract: An efficient and elegant synthesis of alpha(2,8)-oligosialosides is described. The 5-N,4-O-carbonyl-protected sialyl donor undergoes alpha-sialylation in CH2Cl2 to give alpha(2,8)- and alpha(2,9)-disialosides in excellent yields. The 5-N,4-O-carbonyl protecting group was effective in improving the reactivity of the C8 hydroxyl groups toward glycosylation. Using the sialyl building block, the synthesis of tetra-alpha(2,8)-sialic acid was accomplished by using a simple glycosidation and deprotection protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(95 citation statements)
references
References 21 publications
1
92
0
Order By: Relevance
“…Hanashima et al (2009a) reported that the use of silylene/oxazolidinone double-locked sialyl donors in the sialylation reaction affords -sialosides predominantly, even in the non-participating solvent CH 2 Cl 2 . They found that an additional C-5,7-DTBS locking of the 5-N,4-O-oxazolidinone bicyclic sialyl donor 73, which had been originally developed by Tanaka et al (2006) as an -directing sialyl donor, enabled preferential -stereoselectivity in sialylation. The double-locked sialyl donors 74 and 75 show comparable -selectivity with single-locked donor 73 when coupled with the 6-OH galactosyl acceptors 76-78 (Table 8).…”
Section: -Sialosidesmentioning
confidence: 99%
“…Hanashima et al (2009a) reported that the use of silylene/oxazolidinone double-locked sialyl donors in the sialylation reaction affords -sialosides predominantly, even in the non-participating solvent CH 2 Cl 2 . They found that an additional C-5,7-DTBS locking of the 5-N,4-O-oxazolidinone bicyclic sialyl donor 73, which had been originally developed by Tanaka et al (2006) as an -directing sialyl donor, enabled preferential -stereoselectivity in sialylation. The double-locked sialyl donors 74 and 75 show comparable -selectivity with single-locked donor 73 when coupled with the 6-OH galactosyl acceptors 76-78 (Table 8).…”
Section: -Sialosidesmentioning
confidence: 99%
“…4) To resolve this issue, several sialyl acceptors with highly reactive C-4 or C-8 hydroxyl groups have been developed. [17][18][19][20] These are usually equipped with special protection at the C-5 amino group, which probably prevents hydrogen bonding. Recently, we found that the reactivity of 4-OH and 8-OH was greatly ameliorated in 1,5-lactamized sialic acid by glycosylation with sialic acid or another glycosyl donor.…”
Section: Synthesis Of Partially Modified Sialic Acid-containing Glmentioning
confidence: 99%
“…Some donors act by the solvent eŠect using acetonitrile for the regulation of stereoselectivity (11)(12)(13), while the other group utilizes the neighboring group eŠect (11,14). In addition, modiˆcation of the acetamide group at the 5 position was found to elevate a-selectivity (11,(15)(16)(17)(18)(19)(20)(21)(22). Because all of the sialyl donors reported have an ester group at the 1-position (Fig.…”
Section: B Sialylationmentioning
confidence: 99%